2015
DOI: 10.1155/2015/723487
|View full text |Cite
|
Sign up to set email alerts
|

Stress Distribution on Sandwich Structure with Triangular Grid Cores Suffered from Bending Load

Abstract: Triangular grid reinforced by carbon fiber/epoxy (CF/EP) was designed and manufactured. The sandwich structure was prepared by gluing the core and composite skins. The mechanical properties of the sandwich structure were investigated by the finite element analysis (FEA) and three-point bending methods. The calculated bending stiffness and core shear stress were compared to the characteristics of a honeycomb sandwich structure. The results indicated that the triangular core ultimately failed under a bending loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…An initial elastic stage (almost linear) up to a maximum load value (813.3 N for PLA-HYN10) can be seen. Then, the load decreases to values of 520–530 N. This drop is associated with debonding between the skin and the core as reported by Xu et al [ 47 ]. A similar pattern can be observed for PLA-HYN20, with a maximum load after the elastic behavior of 1372.3 N, which is reduced to half after the first debonding signs (see Figure 2 ).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…An initial elastic stage (almost linear) up to a maximum load value (813.3 N for PLA-HYN10) can be seen. Then, the load decreases to values of 520–530 N. This drop is associated with debonding between the skin and the core as reported by Xu et al [ 47 ]. A similar pattern can be observed for PLA-HYN20, with a maximum load after the elastic behavior of 1372.3 N, which is reduced to half after the first debonding signs (see Figure 2 ).…”
Section: Resultssupporting
confidence: 52%
“…These P/W ratios are very interesting and comparable to others reported in the literature with epoxy-carbon fiber (T700) skins (1 mm thick) and different cores (triangular and hexagonal panels, 15 mm thick). Xu et al [ 47 ] reported higher core shear stress values up to 3 MPa as the skin contained carbon fiber and the cores, and was also fiber-reinforced. Nevertheless, the P/W ratios were lower than those obtained in this work, thus showing the interesting properties PLA-honeycombs can provide to composite structures in terms of mechanical properties and lightness.…”
Section: Resultsmentioning
confidence: 99%
“…To validate and compare the results of Arcan samples, standard CT specimens were produced by FFF method using pristine ABS polymers and the SIF, called as fracture toughness, in Mode-I for CT and Arcan samples were compared. According to the ASTM E399 standard, the SIF in the opening mode for CT sample could be calculated using the following equations: where K I is SIF in mode-I and representative fracture toughness of sample in the opening mode of loading, P c is the critical fracture loading, a is the crack length, w and B are the width and thickness of the sample and f(a/w) is the geometry shape function as (Xu et al , 2015): …”
Section: Fracture Toughness Calculationsmentioning
confidence: 99%
“…where K I is SIF in mode-I and representative fracture toughness of sample in the opening mode of loading, P c is the critical fracture loading, a is the crack length, w and B are the width and thickness of the sample and f(a/w) is the geometry shape function as (Xu et al, 2015):…”
Section: Fracture Toughness Calculationsmentioning
confidence: 99%
“…Many authors attempted to determine the equivalent properties of central core by separately modeling the honeycomb core sheet with hexagonal unit cells [1][2][3][4][5][6]. Each cell of the honeycomb sheet periodically repeats itself within inplane direction.…”
Section: Introductionmentioning
confidence: 99%